A Study on Parental Knowledge and Pattern of Medicine Use in Acute Respiratory Infections among Under Five Children in Urban Field Practice Area of Kempegowda Institute of Medical Sciences, Bangalore - Chethana Ramegowda; Prakruthi RA; Pushpa Rajanna (Medsci Publications, 2018)
Introduction: Acute respiratory infections is one of the most im- portant cause of morbidity and mortality in developing and de- veloped countries among under five children and has a public health issue in India. But the knowledge among parents about ARI and its management is low. Hence the present study has been taken up to assess the parental knowledge and pattern of medicine use in acute respiratory infections (ARI). Materials and Methods: Using pre-tested semi-structured proforma, a decriptive study on 100 parents were done after taking informed consent. Information on knowledge of ARI , antibiotics usage and attitude regarding antibiotic use were collected and re- sults were analysed Microsoft excel. Results: 96 % of them said ARI was caused due to exposure to cold, and 60% by Germs.51% used home remedies, 97%subjects were not of aware any vaccines which prevent ARI. 96% heard about antibiotics, among them 59.3% use antibiotics without con- sultation. 1.25% had least attitude regarding antibiotic resistance. Conclusion: Majority had reasonable good knowledge regarding ARI, but lack of knowledge regarding complications of ARI and vaccines available for prevention of ARI. Subjects had unfavour- able knowledge and attitude on antibiotic use.